Influence of High-Performance Work Practices and Public Service Motivation toward Turnover Intention - Jufrianto Kartono (Institute of Computer Science (IOCS), 2021)
The purpose of this research is to investigate and analyze the influence of performance appraisal, compensation, employment security, public service motivation on nurse’s organizational commitment and its impact toward turnover intention. The research model is modified from the previous study and empirically tested on nurses in Xyz hospital in Tangerang during Covid-19 pandemic. Data are collected from hospital nurses on April 2021 and 107 eligible respondents collected through a questionnaire distributed online with simple random sampling technique as sampling technique, then analyzes the data collected using PLS-SEM. The result showed that performance appraisal, employment security, and public service has a significant negative impact towards turnover intention, but compensation doesn’t significantly negatively impact toward turnover intention and all independent variable show significant positive impact toward organizational commitment. The strongest significant negative impact comes from performance appraisal toward turnover intention mediated by organizational commitment. This research confirms some theories on human resource management specifically the impact of employment security and public service motivation towards turnover intention. Moderate predictive accuracy with large predictive relevance was obtained to turnover intention so that it can be developed in further research, there are also managerial implications and recommendations for the further researcher.